ANALISIS PERLINDUNGAN HUKUM TERHADAP INVESTOR DAN BROKER FOREX (FOREIGN EXCHANGE) DALAM PRAKTIK TRADING FOREX ONLINE DI INDONESIA - Kudus, Sergius Utusan; Nubatonis, Orpa J; Jacob, Yossie M. Y (Petitum Law Journal, 2025)
This study aims to examine the legal aspects and protections provided to investors and forex brokers in the practice of online forex trading in Indonesia. The primary legal framework governing forex trading in Indonesia is Law No. 10 of 2011, which amends Law No. 32 of 1997 on Commodity Futures Trading. Although this law does not explicitly mention forex, forex trading falls under the category of derivative contracts as it involves transactions based on the fluctuation of currency exchange rates. This research employs normative legal methods to analyze the relevant regulations. The findings indicate that the Indonesian legal framework offers comprehensive protection to investors and brokers engaged in forex trading. Key protections include strict supervision by the Commodity Futures Trading Regulatory Agency (Bappebti), requirements for the segregation of client funds, prohibitions against market manipulation, and stringent licensing requirements. Additionally, the law provides structured procedures for dispute resolution to ensure fairness and efficiency in resolving conflicts. Both administrative and criminal sanctions are imposed to ensure compliance and integrity in the forex trading market. The existence of Bappebti’s regulations, such as the Electronic Customer Acceptance Regulation in Commodity Futures Trading, further enhances the safety and reliability of online forex trading. Overall, Indonesia's regulatory framework establishes a secure and transparent environment for online forex trading, safeguarding the interests of all parties involved. This ensures that both investors and brokers can engage in trading activities with greater confidence, knowing that robust legal protections are in place.